Analisis Kinerja Bank Syariah - Dian Indiyati; V. Santi Paramitha (Jurnal Ekonomi, 2010)
A bank performance measured by the CAMEL method is a comprehensive indicator of the benefits. Any parties have put interest to the result of value in healthy level, including the management as a successful standard in their administration, Bank Indonesia as the supervision agent, and public as the customer. The study aimed to analyze the performance of bank Syariah with independent operational, Bank Syariah Mandiri and Bank Muamalat Indonesia, by using 4 years-quarterly financial reports. Generally, the study shows that in the research period, Bank Syariah Mandiri has got the healthy in the valuation, while Bank Muamalat Indonesia is sufficient in healthy.